International experience on incentive program in support of fuel economy standards and labelling for motor vehicle: A comprehensive review - Mahlia T.M.I.; Tohno S.; Tezuka T. (2023)
The road transports especially the motor vehicles play a significant role in increment of energy consumption in the transportation sector. However, the harmful greenhouse gas (GHG) emissions from such vehicles which are the main causes of global warming, have been increased as well. One of the effective solutions to reduce the growth rate of energy consumption is the implementation of fuel economy standard and label. Other countries' experiences indicate that the program is very beneficial for society, environment and government. The hierarchy of the program consists of the test procedure, fuel economy standards, fuel economy label and incentive program as a peak of the program. Reviews of the fuel economy standard can be found in many references. However, a few papers deal with the incentive program specifically. Therefore, this paper aims to give a review on the implementation of the incentive program globally in support of fuel economy standard and label for the motor vehicles. Finally, as the incentive program is necessary to support fuel economy standard and label, it should be applied to the motor vehicles as soon as possible. 2013 Elsevier Ltd.